Creative economy: Mental models of cultural entrepreneurs in Belo Horizonte, Brazil - Anna Gabriela Miranda de Oliveira; Marlene Catarina de Oliveira Lopes Melo (The International Journal of Management Science and Information Technology (IJMSIT), 2015)
This study aims to analyze the common elements in the mental models of cultural entrepreneurs in Belo Horizonte, Brazil, as well as to contribute to the expansion of public policies that enable the development of such enterprises. The theoretical framework of this study addresses entrepreneurship and the mental models of entrepreneurs in the creative economy sector. This case study was conducted through multiple semi-structured interviews with five entrepreneurs of cultural enterprises in Belo Horizonte. The collected data indicates common elements of mental models between the entrepreneurs surveyed- most noted were the emotional and symbolic elements that led respondents to explore their mental representations in relation to their endeavors. It was evident, through their responses that their strong connections with their respective companies (almost symbiotic), fueled their motivation and commitment to the success of their enterprises.
Keywords: 650; Entrepreneurship; Mental Models; Creative Economy